Черничная царица: Сказка и стихи / Т. И. Смертина ; худож. М. Шретер - Смертина Татьяна Ивановна (Малыш, 1991)
Экземпляры: аб. ЦБ (20220815) / Инвентарный номер: 16428 / Цена: / Авт.знак: С50 / ББК: Д